ANALYSIS OF RESOURCE BASED-VIEW IN POLITEKNIK PELAYARAN SURABAYA TOWARDS ETO AS COMPETITIVE ADVANTAGE - Siti Fatimah; Rahajeng Galih Ayu Putri Basuki; Agus Prawoto; Elise Dwi Lestari (Jurnal Maritim Malahayati, 2023)
The current world condition has changed quite significantly, the impact of black swans that occurred due to the COVID-19 pandemic contributed quite a lot to the Industrial Revolution 5.0 accompanied by the era of society 5.0 where humans work hand in hand with robots and everything is automation and digitization. This also has an impact on the shipping industry, including commercial ships, where currently individuals who have competence in the field of electrical systems are needed to keep mobilization and business in the maritime industry going on. Through the Standards of Training and Watchkeeping (STCW) all ships sailing currently have the obligation to assign individuals responsible for the electrical system on board the ship, namely the Electro Technical Officer (ETO). Given the high demand and level of urgency by various companies both domestically and abroad for ETO graduates, the Surabaya Shipping Polytechnic decided to open a Diploma III Study Program in Electrical Sailing, and obtained the first graduates in 2016. Based on the results of the analysis, it can be concluded that in Strategy and Operations Management, Politeknik Pelayaran Surabaya has made efforts to improve the quality of education for ETOp graduates, this is reflected in the proportion of budget allocations issued annually, the provision of adequate facilities and infrastructure, the evaluation of the performance and quality of teaching lecturers and educators on a regular basis, the preparation of curriculum and implementation in the form of textbooks and the interaction of teaching patterns with students as well as the existence of quality assurance. This success is reflected by the high absorption of ETO graduates at the Surabaya shipping polytechnic every year where most ETO graduates have been accepted for work within 1-3 months after graduation